Research on the Challenge and Response Strategy of Labor Employment in the Era of Artificial Intelligence - Lin, Shaoyun; Chen, Jiaqi (International Journal of Computer Science and Information Technology, 2024)
The rapid development of information technology has led the world into the era of artificial intelligence. This technological change has a profound impact on the social and economic structure, not only changing people's lifestyle, but also a significant impact on the labor and employment market. The extensive application of artificial intelligence technology has promoted the development of the industry, providing new opportunities for Chinese workers, but at the same time, it has also led to the intensification of large -scale unemployment and structural contradictions in the labor market and the expansion of income gap. In order to effectively respond to these challenges, it is recommended that the state improve the social security system, promote employment and transfer training of unemployed personnel, adjust and optimize the industrial structure, cultivate new growth points of artificial intelligence employment, and strengthen the education and training of artificial intelligence technology, improve the workers Professional skills and literacy to achieve the goal of high -quality employment.